Geochemical Characteristics of Coal in the Taiyuan Formation in the Center and North of the Xishan Coalfield - Gang Wang; Yong Qin; Yiwei Xie (Energies, 2022)
The Xishan coalfield is an important coking coal-producing area in China. The No. 8 and No. 9 coals of the Taiyuan formation were sampled and tested from nine mines in the center and north of the Xishan coalfield, and the coal’s quality characteristics, element occurrence characteristics, enrichment characteristics, and sedimentary environment characteristics were analyzed to provide a foundation for clean and efficient coal utilization and identification of associated coal resources. The results obtained from the experiment show that Li in No. 8 coal is the enrichment element. The enrichment coefficient of the U element of ML8 is 13.78, which is close to the industrial index of recycling. The enrichment hazardous elements are Cu, Mo, Cd of ML8, Mo of DQ8, and Th of ZCD8. Along with K value and Sr/Ba ratio, seawater has a greater influence on the south of No. 8 coal than on the north and on the east of No. 9 coal than on the west. No. 8 coal (except ML8) was formed under an oxidation environment based on the U/Th, Ni/Co, and V/Cr ratios. The oxidation or suboxic to the dysoxic environment resulted in the formation of No. 9 coal. Based on the Al2O3/TiO2 ratio, the sediments of No. 8 and No. 9 coals are mainly from felsic volcanic rocks.